ANTIBIOTIC SENSITIVITY ISOLATION EVALUATION OF MAJOR MICROORGANISMS IN PERIODONTAL TISSUE PATHOLOGY - S.B. Kostenko (Український стоматологічний альманах, 2021)
Relevance of research The loss of effectiveness and activity of antibiotics is caused by their irrational and inappropriate use (especially in self-medication). The risk of antibiotic-resistant mikrobiom potentially be associated not only with time proceeding systemic antibacterial component in the protocol complex treatment of periodontitis but with specific combinations of different used drugs duration, efficiency previously performed mechanical treatment by open or closed curettage, especially the dosing of selected antibiotics middlemen. In – depth study and development of or personalized approaches to treatment is relevant periodontitis by individualizing the choice of appropriate antibiotics for incorporation into the algorithm of complex therapy, or universal approaches, the possibility of implementation of which depends on arguing the effectiveness of a particular combination of antibacterial agents for the vast majority of patients according to studies with sufficient samples. Study Goal is to assess the levels of antibiotic resistance and antibiotic sensitivity of isolates of major microorganisms in periodontal tissue pathology. Materials and methods of research. The research was conducted on the basis of the University Dental Clinic and private dental clinics in Uzhhorod. Determination of levels antibiotic sensitivity was carried out using a disco-diffusion method with the advice and algorithm identified by order MOH Ukraine 05.04.2007 № 167 "On Approval of guidelines" Determination of the sensitivity of microorganisms to antibiotics and in accordance with the recommendations EUCAST (Eurepean Committee on Antimicrobial Susceptibility Testing). During the testing, standard sets of discs with antibiotics and appropriate test cultures were used, which were seeded with microorganisms obtained from patients with generalized periodontitis of varying severity. Research results and their discussion. During the microbiological analysis of smears obtained from periodontal pockets of whole patients study group, microorganisms were identified, which were characterized by relatively high levels of prevalence, among them: P. gingivalis, T. forsythia, F. nucleatum, P. intermedia, A. actinomycetemcomitans, K. pneumoniae, E. coli, E. cloaceae, S. aureus, S. haemolyticus, S. viridans, S. pyogenes. A detailed analysis of the distribution of mean levels of prevalence of antibiotic sensitivity and antibiotic resistance among the analyzed isolates was performed. The results of antibioticograms differ depending on the qualitative and quantitative composition of the isolated microorganisms, their levels of antibiotic sensitivity and antibiotic resistance. This distribution of results indicates the feasibility of a patient-centered approach to treatment, based on the preliminary identification of microorganisms isolated from periodontal pockets of patients, as well as determining the levels of their antibiotic sensitivity and antibiotic resistance. Conclusion. The application of the approach with preliminary determination of antibiotic sensitivity to microorganisms cultured from the oral cavity is characterized by the relevant biological principles of conducting. Prospects for further research. The analysis of the effectiveness of adjuvant antibiotic therapy in the process of complex treatment of periodontal patients and the development of personalized approaches to the treatment of periodontitis are promising.